C4d as a Screening Tool and an Independent Predictor of Clinical Outcomes in Lupus Nephritis and IgA Nephropathy - Yang, Xiaoqian; Yuan, Yanhong; Shao, Xinghua; Pang, Huihua; Che, Xiajing; Cao, Liou; Zhang, Minfang; Xu, Yao; Ni, Zhaohui; Qi, Chaojun; Wang, Qin; Mou, Shan (Frontiers in Medicine, 2022)
Background: As an indispensable marker of complement cascades activation, C4d was confirmed of its crucial role in the pathogenesis of both lupus nephritis (LN) and IgA nephropathy (IgAN). While the studies directly comparing the diagnostic value, and outcomes predicting function of C4d between LN and IgAN are still absent. Methods: A cohort of 120 LN patients, 120 IgAN patients who were diagnosed by renal biopsy between January 2015 and December 2017 and 24 healthy age matched controls were prospectively analyzed. The patients were followed till December 2020. The outcomes were adverse disease treatment response (disease relapse) and kidney disease progression event (decline of estimated glomerular filtration rate by more than 20% or end-stage kidney disease). The renal C4d deposition proportion and pattern were compared between IgAN and LN patients. In addition, the relationship between renal C4d deposition and disease subtypes, disease relapse as well as disease progression for LN and IgAN patients were also analyzed. Results: The LN, IgAN patients and healthy controls were well matched in ages. The follow-up period was 38.5 (30.3-60.8) for LN patients and 45.0 (30.5-57.0) for IgAN patients. 78 patients (65.0%) with LN had renal C4d deposition, compared with only 39 IgAN patients (32.5%) with C4d deposition in renal tissues (P<0.001). The LN patients shared different renal C4d distribution patterns with IgAN patients. Compared with IgAN patients, the C4d deposition in LN patients was significantly more in renal glomerulus (P<0.001) and less in renal tubules (P=0.003). For disease subtypes, renal C4d deposition was especially strong in class V membranous LN and IgAN with tubulointerstitial fibrosis (T1/T2) lesions. Renal C4d deposition was independently correlated with the disease relapse of LN patients (HR=1.007, P=0.040), and acted as an independent predictor of disease progression during the follow-up period for IgAN patients (HR=1.821, P=0.040). Conclusions: Renal C4d distribution proportion and pattern differed between LN and IgAN patients. The presence of C4d in renal tissue acted as an independent predictor of relapse for LN patients and disease progression for IgAN patients.